Yarn on yarn abrasion failure mechanism of ultrahigh molecular weight polyethylene fiber - Sheng, Chunfu; He, Guifang; Hu, Zhongxian; Chou, Chiate; Shi, Jiangao; Li, Jun; Meng, Qingjian; Ning, Xin; Wang, Liming; Ning, Fanggang (Journal of engineered fibers and fabrics, 2021)
Yarns of fiber assemblies such as ropes would abrade with each other during repeated stretching or bending. The yarn on yarn abrasion failure is a main reason for the final assembly failure as the result of the relative movement to each other. To explore the influencing factors and failure mechanism, this work, taking the Ultra High Molecular Weight Polyethylene Fiber (UHMWPE) as the research object, discussed the influences of abrading frequency and the yarn tension on its abrasion life. Based on the observation and analysis of the rising temperatures from abrasion, the abrasion fragments, and morphology of failed yarns, the heating failure and crack propagation mechanisms were proposed, which provide insights into a variety of UHMWPE product designs and applications.